TREND IN PRECIPITATION OVER SUMATERA UNDER THE WARMING EARTH - Iskhaq Iskandar; Muhammad Irfan; Fadli Syamsuddin; Akmal Johan; Pradanto Poerwono (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2011)
A long-term climate variations in the western Indonesian region (e.g. Sumatera) were evaluated using precipitation data as a proxy. The result showed that there was a long-term climate variation over Sumatera region indicated by a decreasing trend in precipitation (drying trend). Moreover, the long-term precipitation trend has a strong seasonality. Remarkable decreasing trend at a rate of 3.9 cm/year (the largest trend) was observed during the northwest monsoon (DJF) season, while the smallest decreasing trend of 1.5 cm/year occurred during the southeast monsoon (JJA) season. This result suggested that the Sumatera Island experienced a drying trend during the northwest monsoon season, and a dryer condition will be more frequently observed during the southeast monsoon season. The long-term precipitation over the Sumatera Island was linked to coupled air-sea interactions in the Indian and Pacific oceans. The connection between the seasonal climate trends and sea surface temperature (SST) in the Indian and Pacific oceans was demonstrated by the simultaneous correlations between the climate indices (e.g. Dipole Mode Index (DMI) and the Niño3.4 index) and the precipitation over the Sumatera Island. The results suggested that both the Indian Ocean Dipole (IOD) and the El Niño-Southern Oscillation Index (ENSO) have significant correlation with precipitation. However, remarkable correlations were observed during the fall transition of the IOD event. Keywords: Climate variations, Dry season, Precipitation, Sumatera and Kalimantan, Wet season.